The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.fct.2018.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of silica-coated iron oxide nanoparticles in human astrocytes

Abstract: Iron oxide nanoparticles (ION) have great potential for an increasing number of medical and biological applications, particularly those focused on nervous system. Although ION seem to be biocompatible and present low toxicity, it is imperative to unveil the potential risk for the nervous system associated to their exposure, especially because current data on ION effects on human nervous cells are scarce. Thus, in the present study potential toxicity associated with silica-coated ION (S-ION) exposure was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 85 publications
(97 reference statements)
2
16
0
Order By: Relevance
“…In SH‐SY5Y cells, the presence of nanoparticles altered the repair of H 2 O 2 ‐induced DNA damage, with considerably more pronounced effects when serum‐free medium was used (Kiliç et al ). However, results obtained from A172 cells were in accordance with the ones found in the present study, with no alteration in repair ability found at any condition tested (Fernández‐Bertólez et al ). This different response between the two types of nervous system cells are in line with the well‐accepted idea that glial cells may have a more efficient repair ability in order to protect neuronal tissue from external insults (Saeed et al ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In SH‐SY5Y cells, the presence of nanoparticles altered the repair of H 2 O 2 ‐induced DNA damage, with considerably more pronounced effects when serum‐free medium was used (Kiliç et al ). However, results obtained from A172 cells were in accordance with the ones found in the present study, with no alteration in repair ability found at any condition tested (Fernández‐Bertólez et al ). This different response between the two types of nervous system cells are in line with the well‐accepted idea that glial cells may have a more efficient repair ability in order to protect neuronal tissue from external insults (Saeed et al ).…”
Section: Discussionsupporting
confidence: 92%
“…However, results obtained from A172 cells were in accordance with the ones found in the present study, Environmental and Molecular Mutagenesis. DOI 10.1002/em with no alteration in repair ability found at any condition tested (Fernández-Bertólez et al 2018a). This different response between the two types of nervous system cells are in line with the well-accepted idea that glial cells may have a more efficient repair ability in order to protect neuronal tissue from external insults (Saeed et al 2015).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations